Eco-efficient construction and building materials : life cycle assessment (LCA), eco-labelling and case studies - Pacheco-Torgal, F. (Woodhead Publishing series in civil and structural engineering., 2014)
Eco-efficient construction and building materials reviews ways of assessing the environmental impact of construction and building materials. Part one discusses the application of life cycle assessment (LCA) methodology to building materials as well as eco-labelling. Part two includes case studies showing the application of LCA methodology to different types of building material, from cement and concrete to wood and adhesives used in building. Part three includes case studies applying LCA methodology to particular structures and components. Reviews ways of assessing the environme.